INTEGRATED MARKETING COMMUNICATION’S IMPACT ON COMMUNICATION CLIMATE SATISFACTION: ROLE OF MEDIA MARKETING AND OWNERSHIP - Musaddag Elrayah; Sanjar Mirzaliev (Fonseca, Journal of Communication, 2025)
This study examines the impact of integrated marketing communication (IMC) on satisfaction with the communication climate, considering the mediating role of marketing in media and the moderating influence of psychological ownership. The research aims to provide empirical evidence on how strategic communication practices enhance internal communication satisfaction within organizations. A quantitative research design was adopted, involving a survey of 249 marketing employees working in different organizations. The study utilized validated scales from past research to measure IMC, marketing in media, communication climate satisfaction, and psychological ownership. Data was analyzed using structural equation modeling (SEM) via ADANCO to test direct, mediating, and moderating relationships. The results indicate that IMC significantly influences satisfaction with the communication climate. Marketing in media was found to mediate this relationship, highlighting the importance of media-based marketing strategies in shaping communication perceptions. Additionally, psychological ownership moderates the effect of IMC on communication climate satisfaction, suggesting that employees with higher ownership perception respond more positively to integrated communication efforts. This study contributes to the literature by integrating IMC with organizational communication perspectives. The findings offer valuable insights for managers aiming to enhance internal communication effectiveness through strategic marketing communication and employee engagement.